Impact on alarm states on the increase in ERTEs - Egido Piqueras, Marto; Egido Mínguez, María (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In this paper we will address the phenomenon of ERTE in Spain in the global context generated by COVID-19. In this respect, we will first analyze the concept of Temporary Layoffs and their regulation within the Spanish legal system. We will then proceed to explore the role that this institute played in dealing with the recent pandemic in our country, comparing it with other similar mechanisms used in other States. In addition, we will highlight the main statistics on the use of ERTE in recent years.